STUDY OF SADDANG RIVER FLOOD CONTROL IN PINRANG DISTRICT SOUTH SULAWESI PROVINCE - Zursyadi
Floods that occur are generally located downstream of the fort dam, namely Dumpanua and Cempa Districts. The area extends to the left and right of the mouth of the Saddang River until the trans bridge bridge trans sulawesi. This flooded subscription area extends to quite fertile settlements, ponds, plantations and rice fields. The purpose of this study is to identify the causes of flooding and the potential for flood inundation at the study sites, namely in the District of Cempa and Duampanua, Pinrang Regency, downstream of the Saddang River. The purpose of this study is to formulate and select structural flood control alternative proposals so that the impact of losses on agricultural production in some villages can be minimized. The stages of this study include collecting / compiling data, conducting literature studies, carrying out statistical analysis of planned rain, carrying out analysis of planned flood discharge, identifying the causes of flooding, knowing the extent of inundation caused by planned flooding, analyzing flood control alternatives structurally through efforts to normalize / excavate river flow and construction / upgrading of dikes. The model used to simulate flood conditions and alternatives used in flood control using the MIKE FLOOD hydraulic model consisting of MIKE 11 and MIKE 21. From the modeling results it is known that the inundation area and the height of inundation in the existing conditions and the conditions for conducting flood control alternatives. In existing conditions, for Q 25 the inundation height was 5.33 m, inundation area was 3.151.95 Ha, and for Q 50 the inundation height was 5.49 m, inundation area was 3.975.04 Ha. There are five alternatives to control the flood of the Saddang River. For the first alternative in the form of normalization on the Paria River with a planned discharge of Q 25, the inundation height of 0.59 m is obtained and the inundation area is 763.67 Ha. and with the discharge of the Q 50 plan, the result is a decrease in inundation height of 0.4 m and a decrease in inundation area of 378.02 Ha. The second alternative in the form of normalization of the Paria River and Babana River with the planned discharge of Q 25 is the result of a decrease in inundation height of 1.40 m and a decrease in inundation area of 1,273.22 Ha. and with the discharge of the Q 50 plan it was found that the inundation height was 0.74 m and the inundation area was 1,550.68 Ha. For the third alternative in the form of normalization on the Paria River, Babana River and Saddang River with the planned discharge of Q 25, the inundation height is 1.47 m and the inundation area is 1,673.84 Ha. and with the discharge of the Q 50 plan, the inundation height is 1.33 m and the inundation area is 1.940.24 Ha. The fourth alternative in the form of tackling on locations experiencing runoff with the planned discharge of Q 50 is the maximum embankment height of the Saddang River 4.26 m, Babana River 4.07 m and Paria River 2,73 m. For the fifth alternative in the form of a combination of normalization on the Paria River, Babana River and Saddang River and the countermeasures at locations with runoff with Q 50 planned discharge, the maximum embankment height for the Saddang River is 2.35 m, Babana River 2.70 m and Sungai Paria 2,74 m. Based on the simulation results on five flood control alternatives, it was found that the optimal results with the flood plan Q 50 were a combination of normalization and retention.